Islamic Republic of Mauritania : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Islamic Republic of Mauritania. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights a continued challenging external environment for Mauritania, with low and volatile metal prices. A steep decline in iron ore prices in 2014-15 took away half of exports, widened the fiscal deficit, put pressure on reserves, and exposed bank vulnerabilities. In response, the authorities adjusted the budget significantly in 2016, allowed the exchange rate to adjust, and mobilized foreign grants and loans. These efforts contributed to reducing external imbalances and maintaining macroeconomic stability. The authorities are now strengthening bank supervision and are preparing a national strategy for accelerated and inclusive growth for 2016-30, including structural reforms and a large-scale, foreign-financed infrastructure investment program to support jobs, growth, and diversification.